The Development of Calculus Teaching Materials using Geogebra - Ari Septian; Darhim Darhim; Sufyani Prabawanto (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study is to find out the calculus teaching material using GeoGebra, knowing the results of expert validation in terms of multimedia and material, and knowing the effectiveness of using calculus teaching material using GeoGebra. The research method used is research and development. The research subjects were 155 students in Departement of Mathematics Education at Universitas Suryakancana. The results of the validation of media experts using the Kendall test, sig. = 0.062 > 0.05 (Ho accepted) means that the calculus teaching material using GeoGebra is feasible to use. The results of the validation of the material using the Kendall test, sig. = 0.065 > 0.05 (Ho accepted) means that the material content is appropriate. The results of tests on 155 students in Departement of Mathematics Education at Universitas Suryakancana, an average percentage of 78% of students answered strongly agree and 15% answered agreed, meaning that calculus teaching material using GeoGebra is effectively used.